Pengaruh Metode Belajar Team Assited Individualization terhadap Prestasi Belajar Statistika pada Mahasiswa Psikologi - Asmadi Alsa (Jurnal Psikologi, 2011)
The new paradigm of learning has placed the students to participate actively in the learning process. One of the consequence is that the learning process must use the variative methods, not only about the transfer of knowledge from teacher to students. This research isaimed to test the impact of Team Assisted Individualization (TAI) to the achievement of Psychology Faculty students in learning Statistics. It is assumesed that the numerical abilityhas a positive correlation to the achievement in studying statistics. So, the respondents numerical ability variabel is controlled using statistics. This research used experiment with Alternative Treatment Posttest Only With Nonequivalent Group Design. Cluster sampling was used to get two of four parallel classes ofStatistics. One class was used randomly as the class taught using TAI and the other class as the control group using conventional teaching method. The numerical ability of the twogroups was tested before getting a different treatment. The teaching with different method was conducted in five sessions.The numerical ability of respondents was tested after the treatment given to the two groups. The mid semester test score of the two groups were compared to the one way covariance analysis with the numerical ability as the covariable. The results indicates that Fscore of the the two groups 10.459, p<0.01. Residual Mean of study achievement for experiment group = 6.997 and control group = 5.464. The result indicates the significant correlation between the numericalal ability and study achievement in statistics (F regression = 43.483, p<0.01 and partial eta squared = 0.316).It can be concluded that there is a significant difference of achievement in studying statistics between the group of students who was taught with Team Assisted Individualizationand with conventional teaching method. The group of students who was taught with Team Assisted Individualization has higher mean score compared to the group taught using the conventional method.